2009
DOI: 10.1017/s0008423909090015
|View full text |Cite
|
Sign up to set email alerts
|

An Austrian Solution for Canada? Problems and Possibilities of National Cultural Autonomy

Abstract: Abstract. Over the last few decades, non-territorial forms of national self-government have attracted increasing interest in political science, especially in the guise of national cultural autonomy. National cultural autonomy is a model of self-government that was pioneered by Austrian theorists and politicians Karl Renner and Otto Bauer in the waning days of the Habsburg Empire, yet was never implemented in Austria–Hungary. This paper will examine some of the problems and possibilities that may attend a trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…8 More speculative publications have suggested that NTA-inspired solutions may break impasses in instances of prolonged (sometimes seemingly intractable) inter-ethnic discord. Proposals have related to Israel (Peled 2013), the Kurds in the Middle East (Gunes 2013; Gunes and Gürer 2018), Cyprus (Dundas 2004), and Canada's indigenous peoples (Nieguth 2009)-treating NTA as yielding untapped potential. Some have considered the application of forms of NTA with a view to promoting Roma rights at the state (Lajcakova 2010) but also international level (Klímová-Alexander 2005).…”
Section: Functionality and Underlying Meanings: From Macro To Micro Perspectivesmentioning
confidence: 99%
“…8 More speculative publications have suggested that NTA-inspired solutions may break impasses in instances of prolonged (sometimes seemingly intractable) inter-ethnic discord. Proposals have related to Israel (Peled 2013), the Kurds in the Middle East (Gunes 2013; Gunes and Gürer 2018), Cyprus (Dundas 2004), and Canada's indigenous peoples (Nieguth 2009)-treating NTA as yielding untapped potential. Some have considered the application of forms of NTA with a view to promoting Roma rights at the state (Lajcakova 2010) but also international level (Klímová-Alexander 2005).…”
Section: Functionality and Underlying Meanings: From Macro To Micro Perspectivesmentioning
confidence: 99%
“…Outside Europe, its adoption has been proposed in respect of Israel (Peled, 2013, pp. 49-51), Turkey (Gunes, 2013) and Canada (Nieguth, 2009). The interesting and original suggestion has also been made that the Roma might be given non-territorial autonomy at EU level (Klímóva-Alexander, 2007, p. 411).…”
Section: Non-territorial Autonomy In Practicementioning
confidence: 99%
“…Theorists, meanwhile, have explored whether FMCs are owed, or indeed already enjoy, constitutionally protected cultural self-rule—what has been termed “non-territorial autonomy” (Chouinard, 2014; Elkins, 1992; Nieguth, 2009; Poirier, 2008, 2012). Representation is often viewed as a corollary of such autonomy (Kymlicka, 1995: 32).…”
Section: National Groups and Consociational Representationmentioning
confidence: 99%